2019
DOI: 10.1039/c9tb01503e
|View full text |Cite
|
Sign up to set email alerts
|

Coral-shaped Au nanostructures for selective apoptosis induction during photothermal therapy

Abstract: The use of coral-shaped Au nanostructures as a heater to selectively induce apoptosis in photothermal therapy of cancer is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[7][8][9] Various NIR-absorbing agents have been designed for PTT, including gold nanostructures (NPs), transition metal sulfides and oxides, organic NPs and carbon-based NPs. [10][11][12][13][14][15][16][17] Among the NIR-absorbing materials, carbon-based nanocomposites, including carbon nanotubes, carbon nanospheres and graphene, stand out owing to their strong NIR absorbance and high laser-heat conversion efficiency, indicating promising prospects for the efficient therapy of osteosarcoma and other deep site tumors. [18][19][20] Though carbon-based biomaterials exhibit ideal biocompatibility, it is evidenced that carbon nanoparticles, particularly carbon nanotubes and graphene, might penetrate the cytomembrane and induce cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Various NIR-absorbing agents have been designed for PTT, including gold nanostructures (NPs), transition metal sulfides and oxides, organic NPs and carbon-based NPs. [10][11][12][13][14][15][16][17] Among the NIR-absorbing materials, carbon-based nanocomposites, including carbon nanotubes, carbon nanospheres and graphene, stand out owing to their strong NIR absorbance and high laser-heat conversion efficiency, indicating promising prospects for the efficient therapy of osteosarcoma and other deep site tumors. [18][19][20] Though carbon-based biomaterials exhibit ideal biocompatibility, it is evidenced that carbon nanoparticles, particularly carbon nanotubes and graphene, might penetrate the cytomembrane and induce cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Under NIR laser irradiation at an ultralow power density (0.25 W/cm 2 ) that is lower than the maximum permissible laser exposure value (0.33 W/cm 2 ) set by the ANSI, mild temperature increases at the local tumor site led to efficient intrinsic cell death with nearly no skin damage, while the probes without the LK peptide or nanobranch modification did not show any significant cell death. Moreover, we have demonstrated that a highly efficient intracellular PTT in vivo at the lowest probe dose (2.5 μg Au) coupled with very low laser power, compared to the previously reported studies, ,,,, is possible with minimal side effects.…”
Section: Results and Discussionmentioning
confidence: 64%
“…Xing et al developed coral-shaped Au nanostructures (Au NCs) with a high surface-to-volume ratio to provide better photothermal conversion in the PPT treatment of breast cancer. Under low-power NIR irradiation for 15 min, Au NCs induced apoptosis in MCF-7 cells by upregulating Bax nuclear-encoded proteins and suppressing Bcl-2 protein expression in the apoptotic pathway, which successfully inhibited cancer recurrence in vivo ( Xing et al, 2019 ).…”
Section: Photothermal Therapy-triggered Apoptosismentioning
confidence: 99%